The Role of Teachers in Enhancing the Interest of Female Students in Arabic Learning at Islamic Boarding School - Mulu, Beti; Gustuti, Welni; Azis, Abdul; Masdin, Masdin; Nurfaidah, Sitti (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2024)
This qualitative study investigates how teachers influence eighth-grade female students' motivation to learn Arabic at an Islamic boarding school in Indonesia. Data were collected through observation, interviews, and documentation and analyzed using Vygotsky's sociocultural framework. Findings were validated through extensive observation and triangulation. The study reveals that teachers enhance students' interest in learning Arabic by fulfilling roles as instructors, mentors, class managers, demonstrators, motivators, and evaluators. This increased interest is reflected in students' enthusiasm, attentiveness, and positive behavior in class. Moreover, factors such as psychological wellbeing, teaching quality, instructional materials, methods, and the learning environment are critical in shaping motivation. The study highlights the pivotal role of teacher involvement and a supportive educational atmosphere in promoting effective Arabic language learning.